From commodity chains to value chains: interdisciplinary theory building in an age of globalization - Sturgeon, Thimoty J. (2013)
This article situates, elaborates, and further explains the theory of global value chain (GVC) governance developed by Gereffi, Humphrey and Sturgeon (2005). The theory of GVC governance at the center of the paper is part of a long-term effort to generalize from accumulated comparative observational research on a range of global industries. First, I discuss the motivations for supplementing the buyer-driven and producer-driven modes of global commodity chain governance developed by Gary Gereffi in the 1990s with an industry-neutral, non-empirical framework. Second, I briefly present the features of the GVC governance framework as they appear in the 2005 article. Third, I discuss the interdisciplinary theoretical underpinnings of the framework in more detail than was possible in the original article. Fourth, I discuss the problem of variation in GVC governance. Fifth, I situate the GVC governance framework in a larger field of GVC-related theory, including but not limited to power and institutions.